2016
DOI: 10.1113/jp271340
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for vascular smooth muscle cell exosomes in calcification and coagulation

Abstract: Vascular smooth muscle cell (VSMC) phenotypic conversion from a contractile to ‘synthetic’ state contributes to vascular pathologies including restenosis, atherosclerosis and vascular calcification. We have recently found that the secretion of exosomes is a feature of ‘synthetic’ VSMCs and that exosomes are novel players in vascular repair processes as well as pathological vascular thrombosis and calcification. Pro‐inflammatory cytokines and growth factors as well as mineral imbalance stimulate exosome secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 94 publications
2
112
0
3
Order By: Relevance
“…Next, we investigated whether exosome/sEV secretion triggers VC. Several studies revealed that both intimal and medial VC follow a common mechanistic pathway, namely increased extracellular vesicle secretion, especially exosomes (40-140 nm in size) in interstitial space [11,60]. Using fetuin-A labelling, Kapustin et al revealed the origin of calcifying exosomes in VSMC [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated whether exosome/sEV secretion triggers VC. Several studies revealed that both intimal and medial VC follow a common mechanistic pathway, namely increased extracellular vesicle secretion, especially exosomes (40-140 nm in size) in interstitial space [11,60]. Using fetuin-A labelling, Kapustin et al revealed the origin of calcifying exosomes in VSMC [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the exosome secretion pathway is activated during VC, and modulations on such a pathway may be applied as novel approaches for VC prevention [8]. During VC progression, the phenotypic transition process involves cytoskeleton remodeling, such as intracellular modifications, which enhanced exosome secretion [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This is highly relevant to the human setting; London and colleagues demonstrated that low turnover bone disease arising from either parathyroid hormone (PTH) resistance or deficiency correlates with vascular calcium load 116 and arterial stiffness or PAD 117 in CKD-MBD. Serum phosphate levels at any level of renal function convey cardiovascular risk, and exert pro-inflammatory actions upon VSM that promote vesicle-mediated vascular mineralization 118, 119 . It has been proposed that the skeleton represent an important “buffer” for phosphate in CKD 120 , and that orthotopic osteoblast –mediated calcium phosphate (as hydroxyapatite) deposition in bone may be responsible for the vascular benefits of normal bone formation.…”
Section: Preclinical Models Of Arterial Calcification In the Setmentioning
confidence: 99%
“…In atherogenesis, contractile SMCs modulate into a proliferative and synthetic phenotype that migrates from the media into the intima, secrete extracellular matrix (ECM) components and build the fibrous cap [5]. Within lesion, SMCs have been assigned broad phenotypic plasticity [5][6][7] and reported to coexist in various intermediate phenotypes. In a recent study, we have shown that SMCs in carotid atherosclerosis downregulate classical and hitherto unknown markers for cytoskeletal integrity as well as calcium (Ca) signaling (i.e.…”
Section: Introductionmentioning
confidence: 99%